History education at the crossroads: Challenges and prospects in a Lesotho context (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The status of History education within a Social Science education framework of the Lesotho educational system is a cause for concern. In an attempt to fosterthe development goals of the Kingdom of Lesotho, education and especially Social Science education were identified as a major role player. In spite of this realisation, History education, and to a lesser extent Geography education was identified as liabilities that could be substituted with other disciplines such as Development Studies. Geography had, however, gradually regained a position as a major Social Science discipline while History education is still considered unimportant in relation to national needs. The evidence is that many schools in Lesotho do not offer History as a subject and both students and teachers of history are not taken seriously as academics. Against this backdrop, this article explores the situation from historical and pedagogic perspectives. I draw considerable examples from contexts such as Cameroon and South Africa, where I have had the opportunity to experience the fragile nature and status of History education both as student and teacher/lecturer. I then suggest why any consideration of Social Sciences with the exclusion of History education will not lead to the desired national goals, thereby justifying the need for a turnaround strategy that favours the teaching and learning of History in Lesotho. The article concludes with recommendations and the prospects for the future, based on the issues raised and discussed.
Keywords: History; Teaching and learning; History education; Lesotho; Heritage